Biosynthesis of Copper Nanoparticles by Cultures from Collection of Microorganisms - Lyudmila I. Zaynitdinova; Javlon J. Tashpulatov; Nikolay A. Lazutin; Rokhila N. Juraeva; Aziza M. Mavjudova (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Biogenic production of copper nanoparticles by bacteria and fungi presents certain scientific and applied interest. In this regard, the ability to synthesize copper nanoparticles by microorganisms from the culture collection of the Institute of Microbiology, which were isolated from polluted areas, was studied. Twenty-one fungal strain and eight bacterial strains were screened, and the biosynthetic activity of representatives of Pseudomonas genus, as the most active biosynthetic of copper nanoparticles, was studied in a comparative aspect. The biosynthetic activity was determined 24-72 hours after adding standard solutions of CuSO4 of different concentration (25 – 50 mg/l by Cu++) to the culture liquid. The formation of nanoparticles was recorded by changing the color of the solution, as well as using UV spectroscopy and atomic force microscopy (AFM). Two strains of Fusarium oxysporum and one strain of Penicillium sp. were found to be the most active among the tested micromycetes. The formation of cubic copper nanoparticles and needle-like structures with a diameter of 800 nm and a length of 40 microns, which were formed as a result of aggregation of cubic nanoparticles with a size of 300-400 nm, has been established. All the tested bacteria showed the ability to synthesize copper nanoparticles, while Pseudomonas stutzeri and Pseudomonas sp. 23 strains expressed the greatest activity and obtained nanoparticles showed high stability. It was also noted that an increase in the initial concentration of copper ions in solution from 25 mg/l to 50 mg/l leads to an increase in the size of the resulting nanoparticles. Based on results of the UV-spectroscopy and AFM microscopy a database of microbial strains synthesizing copper nanoparticles was established, which may be used in future studies.